Testing on mock-ups and on paintings of innovative polymeric gels for surface cleaning - Giulia Rollo (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The research for my MA in Conservation and Restoration has focused on a new class of polymeric hydro-organo gels for cleaning surfaces. The main characteristic of these systems is their high elasticity, which allows them to be peeled from surfaces where they are applied. The assessment of these new cleaning tools has been made through several tests, on mock-ups and real cases. Positive results demonstrated that they could represent, in the future, a valid alternative to traditional cleaning systems.